IMPLEMENTASI BLENDED LEARNING DALAM MEMBANGUN KEMAMPUAN BERPIKIR KRITIS SISWA: IMPLEMENTATION OF BLENDED LEARNING IN DEVELOPING STUDENTS' CRITICAL THINKING SKILLS - M. Yusuf; Barrin Putra Azharin (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2025)
Blended learning has become an important issue in modern education, combining face-to-face and online learning. The background of this study is the need to enhance students' critical thinking skills in the digital era. The problem identified is the lack of empirical evidence regarding the effectiveness of blended learning in this context. This research aims to analyze the impact of blended learning implementation on the critical thinking skills of high school students. The method used is library research, reviewing relevant literature from various academic sources. The results show that blended learning can enhance students' critical thinking skills through interactive and flexible approaches. Effective implementation requires adequate technological support and ongoing teacher training. This study provides significant insights into how blended learning can be applied to develop students' critical thinking skills